2022
DOI: 10.1073/pnas.2209399119
|View full text |Cite
|
Sign up to set email alerts
|

Basaltic reservoirs in the Earth’s mantle transition zone

Abstract: The formation and preservation of compositional heterogeneities inside the Earth affect mantle convection patterns globally and control the long-term evolution of geochemical reservoirs. However, the distribution, nature, and size of reservoirs in the Earth’s mantle are poorly constrained. Here, we invert measurements of travel times and amplitudes of seismic waves interacting with mineralogical phase transitions at 400–700-km depth to obtain global probabilistic maps of temperature and bulk composition. We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The modeling shows that the global average (5.3%) is consistent with a basalt fraction of 18%, which is in excellent agreement with that of pyrolite (Xu et al., 2008). For subduction zones, low density jumps of as much as 4.4 ± 0.3%, which correspond to basalt fractions of 34 ± 6%, favor a moderately basalt‐enriched MTZ, consistent with recent studies (Bissig et al., 2022; Tauzin et al., 2022). This basalt accumulation is associated with the density crossover between basalt and peridotite at 660 km depth, which facilitates the segregation of basalt from its harzburgitic residue and gravitational trapping in the MTZ (Anderson, 1979; Ringwood & Irifune, 1988).…”
Section: Discussionsupporting
confidence: 89%
“…The modeling shows that the global average (5.3%) is consistent with a basalt fraction of 18%, which is in excellent agreement with that of pyrolite (Xu et al., 2008). For subduction zones, low density jumps of as much as 4.4 ± 0.3%, which correspond to basalt fractions of 34 ± 6%, favor a moderately basalt‐enriched MTZ, consistent with recent studies (Bissig et al., 2022; Tauzin et al., 2022). This basalt accumulation is associated with the density crossover between basalt and peridotite at 660 km depth, which facilitates the segregation of basalt from its harzburgitic residue and gravitational trapping in the MTZ (Anderson, 1979; Ringwood & Irifune, 1988).…”
Section: Discussionsupporting
confidence: 89%
“…( 33 ) and Tauzin et al. ( 43 ) first converted their differential travel time observations to depth using a 3D global seismic velocity model (S40RTS) and subsequently found that their estimates of MTZ thickness were consistent with the thicknesses predicted using the updated database, stx11 ( 19 ), for shallow mantle T pot estimates and a PMM composition.…”
Section: Discussionmentioning
confidence: 89%
“…Ritsema et al (51) used a self-consistent thermodynamic database stx08 (34) and found that differential travel times matched predictions from PMM at a T pot consistent with shallow mantle petrological estimates (52)(53)(54) and that PEA required an unrealistically high T pot . Waszek et al (33) and Tauzin et al (43) first converted their differential travel time observations to depth using a 3D global seismic velocity model (S40RTS) and subsequently found that their estimates of MTZ thickness were consistent with the thicknesses predicted using the updated database, stx11 (19), for shallow mantle T pot estimates and a PMM composition.…”
Section: Mtz Temperaturementioning
confidence: 92%
See 2 more Smart Citations